2013
DOI: 10.1002/cne.23435
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and functional expression of Kv4 family α subunits and associated KChIP β subunits in the bed nucleus of the stria terminalis

Abstract: Regulation of BNSTALG neuronal firing activity is tightly regulated by the opposing actions of the fast outward potassium current, IA, mediated by α subunits of the Kv4 family of ion channels, and the transient inward calcium current, IT. Together, these channels play a critical role in regulating the latency to action potential onset, duration, and frequency, as well as dendritic back-propagation and synaptic plasticity. Previously we have shown that Type I–III BNSTALG neurons express mRNA transcripts for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Although we did not observe burst firing in the current study, we have confirmed that the parvocellular PVN neurons, which expressed CRF, also co-expressed Cav 3.1 and Cav 3.2 subunits mediating the I T currents. Conversely, the Type III putative CRF neurons in the BNST do not exhibit low-threshold firing indicative of an I T current (Hammack et al, 2007), but do show significant I A currents (Rainnie et al, 2013). However, in the current study we have shown that the great majority of Type III, putative CRF neurons of the BNST ALG co-expressed Cav 3.3 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe burst firing in the current study, we have confirmed that the parvocellular PVN neurons, which expressed CRF, also co-expressed Cav 3.1 and Cav 3.2 subunits mediating the I T currents. Conversely, the Type III putative CRF neurons in the BNST do not exhibit low-threshold firing indicative of an I T current (Hammack et al, 2007), but do show significant I A currents (Rainnie et al, 2013). However, in the current study we have shown that the great majority of Type III, putative CRF neurons of the BNST ALG co-expressed Cav 3.3 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell recordings were obtained as previously described (Rainnie, Hazra et al 2014). Neurons were patched using one of three different recording patch solutions depending on the experiment being done.…”
Section: Preparation Of Bnst Slices and Patch Clamp Recording-mentioning
confidence: 99%
“…Kv4.2 and Kv4.3 are major mediators of I to or I A in nervous system and heart [3,4], and their blockage or dysfunction is associated with pathologies, including pain, epilepsy, atrial fibrillation and long QT syndrome [5,6,7,8]. However, our understanding on the gating mechanism and structural characteristics of Kv4 channels is much less advanced compared to the Kv1 channel family.…”
Section: Introductionmentioning
confidence: 99%